EFFECT OF THE ROLE OF FAMILY PLANNING OFFICER ON PARTICIPATION OF FAMILY PLANNING PLAN (CONDOM AND VASECTOMY) IN THE SOUTH PURWOKERTO - Elsa Berlianti Hasibuan; Bambang Hariadi; Colti Sistiarani (Kesmas Indonesia, 2018)
Background: As an Efforts to increase male participation of family planning is needed a socialization about male contraception through the role of family planning officer who have roles as extension agents, facilitators, motivators, dynamists and catalysts in mobilizing public especially in district. The purpose of this study was to determine the influence of family planning officer roles as an extension agent, as facilitator, as motivator, as Dynamist and as catalyst for male participation in family planning (condoms and vasectomy) in the South Purwokerto. Methods: This research is a quantitative research using cross-sectional approach. Population of Male Couple Age Fertile in South Purwokerto Sub-district, where the number of Couple Age Fertile are 11,442 with sample there are 88 Male Couples Age of Fertile. The analysis used univariate analysis, bivariate with chi square and multivariate with logistic regression. Results: The result of bivariate analysis that there is effect: the role of family planning officer as Extension (p = 0,000), as Facilitator (p = 0,000) and as Motivator (p = 0,000). The result of bivariate analysis that there is no effect: the role of family planning officer as Dynamicator (p = 1,000) and as Catalyst (p = 0,830). Multivariate analysis results there is an effect on: The role of family planning officer as Extension, as Facilitator, and as Motivator Conclusion: the role of family planning officer has effect as Extension, as Facilitator, and as Motivator for Men's Participation in Family Planning (Condom and Vasectomy).